1996
DOI: 10.1073/pnas.93.15.8016
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala activity at encoding correlated with long-term, free recall of emotional information.

Abstract: Positron emission tomography of cerebral glucose metabolism in adult human subjects was used to investigate amygdaloid complex (AC) activity associated with the storage of long-term memory for emotionally arousing events. Subjects viewed two videos (one in each of two separate positron emission tomography sessions, separated by 3-7 days) consisting either of 12 emotionally arousing film clips ("E" film session) or of 12 relatively emotionally neutral film clips ("N" film session), and rated their emotional rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
488
4
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 797 publications
(555 citation statements)
references
References 39 publications
48
488
4
9
Order By: Relevance
“…These findings corroborate a recent human case study which reports that lesions in the left amygdala cause encoding and long-term memory deficits for emotionally arousing words, but have no effect on memory for neutral words (Claire, Sophie, Claudia, Philippe, & Eliane, 2015). Neuroimaging research in healthy participants reveals a positive correlation between bilateral amygdala activity during the encoding of emotional films and recall performance for film content three weeks later (Cahill et al, 1996;Canli, Zhao, Brewer, Gabrieli, & Cahill, 2000). Similar results have been found in MDD patients who, relative to control participants, exhibit increased right amygdala activity in response to negative emotional images which predicts superior recall for those images one week later, and correlates with depressive symptom severity (Hamilton & Gotlib, 2008).…”
Section: The Role Of Rem Sleep and Amygdala Function In Emotional Memorysupporting
confidence: 89%
“…These findings corroborate a recent human case study which reports that lesions in the left amygdala cause encoding and long-term memory deficits for emotionally arousing words, but have no effect on memory for neutral words (Claire, Sophie, Claudia, Philippe, & Eliane, 2015). Neuroimaging research in healthy participants reveals a positive correlation between bilateral amygdala activity during the encoding of emotional films and recall performance for film content three weeks later (Cahill et al, 1996;Canli, Zhao, Brewer, Gabrieli, & Cahill, 2000). Similar results have been found in MDD patients who, relative to control participants, exhibit increased right amygdala activity in response to negative emotional images which predicts superior recall for those images one week later, and correlates with depressive symptom severity (Hamilton & Gotlib, 2008).…”
Section: The Role Of Rem Sleep and Amygdala Function In Emotional Memorysupporting
confidence: 89%
“…Kensinger and Corkin (2004) have suggested that two different pathways for the effects of valence and arousal exist in the human brain. For arousing items, the amygdala plays a critical role in memory enhancement, which is supported by imaging work in this area (Cahill et al, 1996;Canli et al, 2000). In contrast, the effects of valence appear to be in part modulated by the prefrontal cortex .…”
Section: Discussionmentioning
confidence: 88%
“…Healthy male subjects showed increased connectivity between the right but not the left amygdala and the pulvinar and superior colliculus during presentations of unseen (masked) fearconditioned faces compared to seen (unmasked) fearconditioned faces (Morris et al 1999). The glucose metabolic rate of the right but not the left amygdala in healthy subjects, who were viewing emotionally arousing (aversive) film clips, was highly correlated with their long-term memories of these films (Cahill et al 1996). Another PET study has implicated activation of the right amygdala in traumatic autobiographical memories (Rauch et al 1996).…”
Section: Discussionmentioning
confidence: 91%